2022
DOI: 10.1007/s00277-022-05043-y
|View full text |Cite
|
Sign up to set email alerts
|

Monocytosis at the time of diagnosis has a negative prognostic impact in myelodysplastic syndromes with less than 5% bone marrow blasts

Abstract: The prognostic impact of monocytosis has not yet been determined in patients with myelodysplastic syndromes (MDS). We examined absolute monocyte counts in the peripheral blood at the time of diagnosis in 1949 patients with a bone marrow blast count < 5%, a condition we call MDS < EB1 (MDS with a blast percentage lower than that of MDS with excess blasts 1, according to the WHO classification). Monocytosis (> 600/µl) was associated with higher median hemoglobin, WBC, and ANC, and more favorable karyoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…and Silzle et al., which, in a population of MDS with low blast count, have recently shown that monocytosis >0.6 x10 9 /L is associated with a shorter OS, also in the subtype enriched with RS. This suggests that MDS with monocytosis and CMML with RS may be located in a “gray zone” that makes diagnosis challenging but, on the other hand, supports a therapeutically similar approach in these cases ( 14 , 15 ). Altogether, this study supports the notion that classifications based on selected clinical characteristics, generally with arbitrarily chosen thresholds, have always inherent limitations.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…and Silzle et al., which, in a population of MDS with low blast count, have recently shown that monocytosis >0.6 x10 9 /L is associated with a shorter OS, also in the subtype enriched with RS. This suggests that MDS with monocytosis and CMML with RS may be located in a “gray zone” that makes diagnosis challenging but, on the other hand, supports a therapeutically similar approach in these cases ( 14 , 15 ). Altogether, this study supports the notion that classifications based on selected clinical characteristics, generally with arbitrarily chosen thresholds, have always inherent limitations.…”
Section: Discussionmentioning
confidence: 84%
“…On the other hand, monocytosis (monocyte count >0.6 x10 9 ) is not uncommon in patients with MDS with low blast count (< 5%). Within the RS phenotype, 20% of patients show monocytosis and there seems to be a positive correlation between the percentage of RS and absolute monocyte count, with the overall survival (OS) being significantly shorter ( 14 ). Moreover, the absolute monocyte count at diagnosis may affect the prognosis in MDS independently of the Revised International Prognostic Score System (IPSS-R) risk score, and monocytopenia (<0.2 x10 9 /L) may be associated with a higher risk of acute myeloid leukemia (AML) transformation ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sihem Tarfi, 1,2 Quentin Barathon, 2 Bouchra Badaoui, 2 Nicolas Freynet, 2 Vincent Parinet, 1,5 Mathieu Leclerc, 1,5 Sébastien Maury,…”
Section: Authorsunclassified
“… 9 The mean number of mutations per sample in CMML-like MDS patients (3.5±0.2) was the same as that of CMML patients (3.5±0.3) and significantly higher than that of other MDS patients (1.7±0.3; P ≤0.0001, unpaired t test with Welch’s correction). In the learning cohort, TET2 was the most frequently mutated gene in the three groups of patients, with a similar proportion of patients carrying at least one TET2 mutation in CMML (68.2%) and CMML-like MDS (66.7%) ( P =0.92, Χ 2 test) while this proportion was lower in other MDS (34.6%; P =0.036, Χ 2 test) ( Figure 1E ).…”
mentioning
confidence: 91%
See 1 more Smart Citation